Analisis Penggunaan Media Interaktif Berbasis PowerPoint dalam Pembelajaran IPAS di Kelas III SD - Siti Sholihah; Sita Isna Malyuna; Sumadi Sumadi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aims to examine the use of interactive PowerPoint-based learning media in IPAS instruction for third-grade elementary school students on metamorphosis material. The research was conducted to address students’ low interest, participation, and understanding caused by conventional teaching methods and limited media variation. Since metamorphosis is an abstract concept, interactive media are needed to support meaningful learning.This study employed a descriptive qualitative approach. Data were collected through observations and interviews involving third-grade teachers and students at SD Pelang, selected using purposive sampling. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion verification. The findings showed that interactive PowerPoint-based learning media increased students’ interest and participation in learning. The media also facilitated understanding of metamorphosis concepts through engaging visual and interactive presentations and positively affected students’ cognitive learning outcomes. These results are supported by a review of eight previous studies indicating that interactive PowerPoint-based media have high validity, practicality, and effectiveness in IPAS learning. The findings showed that interactive PowerPoint-based learning media increased students’ interest and participation, facilitated understanding of metamorphosis concepts through engaging visual presentations, and improved cognitive learning outcomes. These findings are supported by a review of eight previous studies indicating high validity, practicality, and effectiveness of interactive PowerPoint-based media in IPAS learning. Therefore, this media can be considered a viable alternative for improving learning quality in elementary schools. Future studies are recommended to involve broader samples and different research approaches.